THE ROLE OF NURSES IN PRIMARY HEALTH CARE SERVICES IN IMPROVING THE HEALTH OF ADOLESCENT GIRLS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
A healthy lifestyle (HLS) is a rational way of life whose integral feature is active effort aimed at preserving and improving health. A lifestyle that promotes public and individual health constitutes the basis of prevention, and shaping it is an important task of the state’s social policy on protecting and strengthening public health.